A normalized frequency-domain block filtered-x LMS algorithm for active vehicle interior noise control. (1st April 2019) - Zhang, S.; Wang, Y.S.; Guo, H.; Yang, C.; Wang, X.L.; Liu, N.N.
Highlights: A novel normalized frequency-domain block FxLMS algorithm is proposed. The NFB-FxLMS algorithm is used for ANC of vehicle interior noise. The calculation amount of NFB-FxLMS algorithm is considerably reduced. NFB-FxLMS algorithm has better stability and convergence performance. NFB-FxLMS is effective on interior noise reduction in the entire frequency band. Abstract: A novel normalized frequency-domain block FxLMS (NFB-FxLMS) algorithm is proposed for active vehicle interior noise control. Different from the time-domain FxLMS (TD-FxLMS) algorithm that processes noise data point by point, the NFB-FxLMS algorithm processes noise data block by block based on the fast Fourier transform (FFT) and the overlap–save method, such that the calculation amount is considerably reduced. In the process, the input signal of a control filter and the filtered input signal are transferred to frequency domain, respectively. Meantime, its convergence performance is improved by normalizing each frequency-domain bin. The interior noise of a high-speed vehicle is recorded and analyzed. The simulations of ANC based on the TD-FxLMS, normalized TD-FxLMS (TD-NFxLMS), basic FB-FxLMS, and NFB-FxLMS algorithms are performed. The results show that the interior noises are suppressed by these four algorithms. But the NFB-FxLMS with greater stability has faster convergence rate and lower steady-state error in the entire frequency band compared with other three algorithms. The higher the vehicle speed, the more obvious the advantages of the NFB-FxLMS. Furthermore, the NFB-FxLMS shows very good effect on nonstationary noise. The NFB-FxLMS algorithm can be directly used in an active interior noise control system of the sample vehicle, which can be extended to other types of vehicle for interior noise control.